In the forest - Ets, Marie Hall, 1895- (New York, Puffin Books, 1972)
The animals join a young boy as he walks through the forest blowing his new horn.
"First published September 1944."
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Booklist
3.6
K-3
Keywords: Animals -- Fiction; Animals -- Fiction